An evaluation of the feasibility and usability of a proof of concept mobile app for adverse event reporting post influenza vaccination. Issue 7 (2nd July 2016) - Wilson, Kumanan; Atkinson, Katherine M.; Westeinde, Jacqueline; Bell, Cameron; Marty, Kim; Fergusson, Dean; Deeks, Shelley L.; Crowcroft, Natasha; Bettinger, Julie A.
ABSTRACT: The Canadian National Vaccine Safety network (CANVAS) gathers and analyzes safety data on individuals receiving the influenza vaccine during the early stages of annual influenza vaccination campaigns with data collected via participant surveys through the Internet. We sought to examine whether it was feasible to use a mobile application (app) to facilitate AEFI reporting for the CANVAS network. To explore this, we developed a novel smartphone app, recruited participants from a hospital influenza immunization clinic and by word of mouth and instructed them to download and utilize the app. The app reminded participants to complete the CANVAS AEFI surveillance surveys ("AEFI surveys") on day 8 and 30, a survey capturing app usability metrics at day 30 ("usability survey") and provided a mechanism to report AEFI events spontaneously throughout the whole study period. All survey results and spontaneous reports were recorded on a privacy compliant, cloud server. A software plug-in, Lookback, was used to record the on-screen experience of the app sessions. Of the 76 participants who consented to participate, 48(63%) successfully downloaded the app and created a profile. In total, 38 unique participants completed all of the required surveillance surveys; transmitting 1104 data points (survey question responses and spontaneous reports) from 83 completed surveys, including 21 usability surveys and one spontaneous report. In total, we received information on new or worsening health conditions after receiving the influenza vaccine from 11(28%) participants. Of the usability survey responses, 86% agreed or strongly agreed that they would prefer to use a mobile app based reporting system instead of a web-based system. The single spontaneous report received was from a participant who had also reported using the Day 8 survey. Of Lookback observable sessions, an accurate transmission proportion of 100% (n=290) was reported for data points. We demonstrated that a mobile app can be used for AEFI reporting, although download and survey completion proportions suggest potential barriers to adoption. Future studies should examine implementation of mobile reporting in a broader audience and impact on the quality of reporting of adverse events following immunization.